Educational Intervention and Remediation in the Light of the Competency-Based Approach - abboud, ourida (El Omda in Linguistics and Discourse Analysis, 2019)
The competency-based approach is a comprehensive educational methodology and a type of existential perspective on educational issues. It ultimately emphasizes developing a learner who is self-confident and capable of effectively fulfilling their social role and facing life’s challenges. This approach supports effective education aimed at building a well-rounded and balanced personality across all dimensions: physically, mentally, intellectually, emotionally, socially, and humanly.